The improvement value and treatment safety of neurological rehabilitation strengthening training on upper limb functions of patients with cerebrovascular diseases - YOU,Fei (2022)
Abstract To explore the improvement value and treatment safety of neurological rehabilitation strengthening training on upper-limb functions of cerebrovascular patients. A total of 80 patients with cerebrovascular hemiplegia were divided into two groups. The 40 patients in the regular group were instructed to carry out regular rehabilitation training for 20 min/day, lasting for 5d/week; another 40 patients in the strengthening group were instructed to carry out neurological rehabilitation strengthening training on the basis of regular training. Before the intervention, there was no significant difference in fma-ue, ARAT, MBI scores and EDV, RI, PSV of carotid and vertebral arteries between the two groups (P > 0.05); after treatment, fma-ue, ARAT, MBI, EDV, PSV of the study group were higher than those of the control group, RI was less than that of the control group, the differences were statistically significant (P<0.05), after the intervention, the number of patients with grade IV ~ VI in the study group was more than that of the control group, the difference was statistically significant (P<0.05). The application of neurological rehabilitation strengthening training might improve the upper-limb motor functions of patients with cerebrovascular hemiplegia and promote the rehabilitation of limb nerve functions.